LANGUAGE FUNCTIONS USED BY THE MAIN CHARACTER IN “12 YEARS A SLAVE” MOVIE TRANSCRIPT - Yulistiono, Risnu Freli (Jurnal Bahasa Lingua Scientia, 2015)
Language is an instrument of communication. Language carries functions through which the intention of communication can be revealed. This study investigates language functions used by the main character in “12 Years a Slave” movie transcript by Stave Mc Queen. The objectives of the study was to find out the types of language functions used by main character in the movie and to describe the most dominant types of language functions found based on Roman Jakobson’s theory. The research design of this research was descriptive method with qualitative approach. The result showed that Solomon Northup as the main character in “12 Years a Slave” movie transcript by Stave Mc Queen used all types of the language functions in the movie. They are; 43 emotive, 17 directive, 8 phatic, 4 poetic, 117 referential and 10 metalinguistic function. Referential function becomes the dominant types of language function used by the main character in “12 Years a Slave” movie transcript by Stave Mc Queen. Referential function is used dominantly by Solomon Northup as the main character, because as a slave, he tried to reveal the truth by correlating every piece of evidence and giving information about his life that he was a free man not a slave that run away from other country.